2022
DOI: 10.1038/s41467-022-31904-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin 1 and its inhibitory ligand mini-tryptophanyl-tRNA synthetase inversely regulate VE-cadherin turnover and vascular permeability

Abstract: The formation of a functional blood vessel network relies on the ability of endothelial cells (ECs) to dynamically rearrange their adhesive contacts in response to blood flow and guidance cues, such as vascular endothelial growth factor-A (VEGF-A) and class 3 semaphorins (SEMA3s). Neuropilin 1 (NRP1) is essential for blood vessel development, independently of its ligands VEGF-A and SEMA3, through poorly understood mechanisms. Grounding on unbiased proteomic analysis, we report here that NRP1 acts as an endocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 105 publications
0
12
0
Order By: Relevance
“…Tryptophanyl-tRNA synthetase 1 (encoded by WARS1 ) exists in both secreted and intracellular forms 37 , with downstream impacts on vascular permeability 38 . Here, we found a cis -sQTL for excision of exon 10 of WARS1 (encoding a portion of the tRNA synthetase protein domain), which colocalized with both the WARS1 pQTLs and risk for hypertension in FinnGen (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Tryptophanyl-tRNA synthetase 1 (encoded by WARS1 ) exists in both secreted and intracellular forms 37 , with downstream impacts on vascular permeability 38 . Here, we found a cis -sQTL for excision of exon 10 of WARS1 (encoding a portion of the tRNA synthetase protein domain), which colocalized with both the WARS1 pQTLs and risk for hypertension in FinnGen (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…The adapter molecule synectin is an important intracellular binding partner of NRP1 and facilitates myosin IV-mediated endocytosis (Cai and Reed, 1999, Naccache et al, 2006). A recent study also found that NRP1 interacts with members of the ERM family of intracellular proteins, which act as intermediaries between the plasma membrane and actin cytoskeleton and that have also been associated with endocytosis and intracellular trafficking (Ponuwei, 2016, Gioelli et al, 2022). NRP1 may thus function not just as a co-receptor, but also as a linker to mediate the intracellular trafficking of cell surface receptors.…”
Section: Discussionmentioning
confidence: 99%
“…This idea is supported by studies showing that NRP1 co-ordinates PDGFRα internalisation and its intracellular signalling, as well as the trafficking of integrin α5β1 during cell adhesion (McGowan and McCoy, 2021). Furthermore, it has recently been shown that NRP1 binds to VE-Cadherin and regulates its cell surface turnover, a role that has been proposed to at least partly explain its role in EC barrier integrity (Gioelli et al, 2022, Bosseboeuf et al, 2023). In response to VEGFA the cytoplasmic domain of NRP1, which binds synectin, has been found to be crucial in mediating NRP1’s positive regulation of leakage (Fantin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Regions of turbulent flow in vessels are the major sites of atherosclerosis, the pathological process that narrows blood vessels, reducing oxygen and nutrient delivery to tissues. Recent evidence shows that the plasma membrane pool of NRP1 colocalises with VE-cadherin at cell-cell adhesion sites where it interacts with VE-cadherin [ 58 , 59 ]. NRP1 modulates AJs dynamics in ECs cultured in static conditions [ 58 ] and AJs stability in ECs exposed to laminar flow [ 59 ].…”
Section: Signalling Cross-talk Mediated By Nrp1mentioning
confidence: 99%